MENINGKATKAN KEMAMPUAN MENDENGAR SISWA MELALUI PERMAINAN CHAIN WHISPERS - Ahmad Wael; Rezkiah Hartanti; Hayat Marwan Ohorella; Ruslan; Dian Saputra (Qalam : Jurnal Ilmu Kependidikan, 2023)
The purpose of this study is to improve students' listening skills using a series of whispering games. The subjects of this study were eighth-grade high school students of SMP Negeri 7 Sorong City. The data of the students were obtained from tests used as instruments in this work, the use of methods in this work was experimentally quantitative. The research instrument was a pre-test to determine students' listening skills, and a post-test was used to investigate the use of a series of whispering games to improve students' listening skills. The results of this study showed differences in the pretest and posttest scores of 28 students. The purpose of these two tests is to find out how well students can hear, and then based on these tests, the authors calculate the students' scores, and the researchers conclude that string whispering improves students' listening. SMP Negeri 7 Kota Sorong for eighth-grade students. The purpose of this research is to improve students' listening skills and how students understand what the teacher intends Keywrod : chain whisper game, student listening skill.